The ethical-political dimension as constitutive of political psychology - Alessandro Soares da Silva; Vinícius Furlan (Estudos de Psicologia (Campinas), 2025)
Abstract Objective This theorical essay aimed to understand how ethics in Political Psychology is constituted by the ethics-politics syntagma, in wich its ethical rationality is its political rationality. Method A literature review was carried out since Machiavelli, in wich politics has been understood as the technique of the act of governing, totally divorced from its ethical dimension. Results In Political Psychology, the ethical axiomatics is politics itself. Its politics lies precisely in its ethical dimension. In Aristotelian terms, Political Psychology shapes itself as a praxis, that is, as an ethics, from which its political dimension is not detached. The issue of ethics concerns the political positions that its theoretical systematization occupies in the context of contemporary culture in the face of the challenges that emanate from it. And its axiological axes find value in the notions of justice and freedom. Conclusion Thus, politics in Political Psychology is about ethics. Its political practice is, in the stricto sensu, its ethical practice. Its ethical-political axiological dimension is ultimately aimed at human freedom.